A modern view on the management of patients with ulcerative colitis of mild and moderate severity in outpatient practice - A. M. Kharitidis; O. B. Shchukina (Лечащий Врач, 2022)
The article discusses modern approaches to the treatment of ulcerative colitis. It is indicated that for the choice of tactics and treatment algorithm, the extent of the lesion, as well as the severity of the current exacerbation, classified as mild, moderate and severe, are important. The criteria are useful for assessing the need for hospitalization, but do not take into account such important signs as nocturnal symptoms, extraintestinal manifestations, endoscopic activity. The severity of an exacerbation of a disease characterizes its severity at the moment, but may not reflect the long-term cumulative burden of the disease. The extent of the lesion, in turn, may influence the choice of route of administration. There are: proctitis (spread of inflammation to the rectosigmoid angle), left-sided (inflammation is limited to the splenic flexure) and widespread lesion (inflammation extends proximal to the splenic flexure, including pancolitis). To achieve the goals of therapy, the time period from the start of treatment to the expected clinical response, remission and endoscopic healing was determined. The immediate and short-term goals are clinical response and remission, as well as the normalization of the level of C-reactive protein. Reduction of fecal calprotectin to the optimal range is recommended as an official intermediate treatment goal. The degree of increase in the concentration of fecal calprotectin correlates with the severity of inflammation, and with a mild degree of the disease, its values may be normal or borderline. In this situation, repeated monitoring of fecal calprotectin over time can clarify the clinical picture. This was demonstrated in a recent prospective cohort study, where consistent determination of fecal calprotectin at 1-month intervals was the best predictor of exacerbation before the onset of clinical symptoms. Along with endoscopic mucosal healing, the long-term goal is to restore the quality of life and the absence of disability. The article discusses the use of drugs of the mesalazine group, topical and systemic steroids for the treatment of ulcerative colitis, as well as approaches to monitoring the disease and long-term management of patients.